Estudio, análisis e implementación de un motor eléctrico como fuente de potencia para un vehículo tubular. - Salinas Masache, Carlos Alberto (2018)
Firstly, the necessary power of the electric motor is determined, for which it was necessary to know the general characteristics of the vehicle. Then, the forces that oppose the movement were analyzed, such as: aerodynamic, rolling, gravitational and resistance to inertia. Thus, this analysis determines the total resistance of the vehicle, this being the main value that allowed to determine the power of the electric motor In this research, the different stages for the study and implementation analysis of an electric motor are detailed, as a power source for a tubular vehicle, with the purpose of fulfilling the objectives set out in this research project. Later, the type of engine that is going to be used is analyzed, taking into account factors such as: type of engine and power, cost, physical structure, weight and so on, to then be implemented in the tubular vehicle. Finally, performance tests are made to evaluate the vehicle’s work. In this sense, by a concrete road of flat surface and with slope a route was made; of which it is known the value of the speed reached and the autonomy offered by the tubular vehicle.